Pengaruh Faktor Eksternal dan Internal terhadap Minat Mahasiswa Memilih Karir sebagai Wirausaha - Kukuh Mulyanto (Jurnal Ilmiah Aset, 2021)
This study aims to determine the effect of external and internal factors on intention students to entrepreneur career. The population used in this study were student in STIE Anindyaguna and STTPati which amounts to 100 people. Method of sampling technique in this study carried with purposive sampling. The analysis tool used is the technique of path analysis. The results obtained in this study is the positive effect of external and internal factors on intention students to entrepreneur career.